Circular RNA circASPM promotes the progression of glioblastoma by acting as a competing endogenous RNA to regulate miR-130b-3p/E2F1 axis - Hou, Dianqi; Wang, Zhenlin; Li, Haimeng; Liu, Juan; Liu, Yaohua; Jiang, Yang; Lou, Meiqing (Journal of cancer, 2022)
Background: Glioblastoma Multiform (GBM) is the primary malignancy with the highest incidence and worst prognosis in the adult CNS. Circular RNAs (circRNAs) are a novel and widely diverse class of endogenous non-coding RNAs that can promote or inhibit gliomagenesis. Our study aimed to explore the role of circASPM in GBM and its molecular mechanism. - Methods: Levels of circASPM, miR-130b-3p and E2F1 were determined by quantitative real-time PCR (qRT-PCR) or western blotting assay. MTS, Edu, neurospheres formation and extreme limiting dilution assays were used to detect the tumorigenesis and proliferation of GSCs in vitro. The interactions between miR-130b-3p and circASPM or E2F1 were demonstrated via qPCR, western blotting, dual-luciferase reporter and RNA immunoprecipitation (RIP) assays. Xenograft experiments were used to analyze tumor growth in vivo. - Results: CircASPM was overexpressed in GBM and promoted the tumorigenesis and proliferation of GSCs both in vitro and in vivo. Mechanistically, circASPM up-regulated the expression of E2F1 in GSCs via miR-130b-3p sponging. We furtherly demonstrated that circAPSM could promote the GSCs proliferation via E2F1 up-regulating. Therefore, our study identified a novel circRNA and its possible mechanism in the development and tumorigenesis of GBM. - Conclusions: CircASPM can promote GBM progression via regulating miR-130b-3p/E2F1 axis, suggesting that circAPSM could provide an effective biomarker for GBM diagnosis and prognostic evaluation and possibly being used for molecular targeted therapy.
Gesehen am 04.06.2022